Implementation of the General Spatial Planning Policy for the Jatinangor Urban Area, Sumedang Regency, West Java Province - Christine Ray Indah Dachi; Muhadam Labolo; Didik Suprayitno (Department of Public Administration, 2023)
With abundant wealth, the Indonesian state has valuable resources for developing its country. Therefore, development needs to be carried out evenly in various regions throughout Indonesia. Unfortunately, however, the spatial conditions in the urban area of Jatinangor, which develop naturally and are not planned, give rise to various complex problems. This study then aims to see how the policy implementation of the General Spatial Plan for the Jatinangor Urban Area, Sumedang Regency, West Java Province. The method used in this study uses a qualitative method with an inductive approach. Data analysis will be carried out using a SWOT analysis. Research data comes from interviews and literature studies. The results of this study then found that, in practice, implementing the general spatial plan for the Jatinangor urban area was influenced by factors such as policy content, information, support, and potential distribution. Through the SWOT analysis results, at least five strategies were found in overcoming various obstacles to implementing the general spatial plan for the Jatinganor urban area. These strategies include making KPJ one of the regional priorities for Sumedang Regency; increasing the commitment of implementers in managing the urban area of Jatinangor; facilitating lands whose types of use have been determined according to the detailed spatial layout plan; preparing a detailed spatial plan (RDTR) for Jatinangor District; and make a monitoring and evaluation schedule for each stage of the implementation of KPJ management